Marriage Validity and Divorce Resolution in Islamic Law Perspective: Keabsahan Perkawinan dan Penyelesaian Perceraian dalam Perspektif Hukum Islam - Stefany, Inge Bethzeda; Phahlevy, Rifqi Ridlo (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Marriage and divorce are central issues in Islamic family law and need to be analyzed in the context of modern society. Specific Background: Many divorce cases arise due to infidelity and communication breakdown, creating challenges for legal and social resolution. Knowledge Gap: Few studies analyze court decisions comprehensively by combining Islamic law interpretation and legal practice. Aim: This study aims to examine marriage validity and divorce resolution from the perspective of Islamic law and statutory regulations. Results: The study reveals that court decisions are largely consistent with Islamic principles but highlight areas requiring better public understanding of legal grounds for divorce. Novelty: This research integrates legal analysis with social implications, providing a holistic view of divorce resolution. Implications: Findings suggest the need for strengthening legal literacy and counseling programs to reduce preventable divorce cases. Highlights : Marriage validity and divorce law reviewed Islamic law and legal practice integrated Recommendations for counseling and education Keyword: Marriage Law, Islamic Family Law, Divorce Resolution, Court Decision, Legal Analysis